Improving Students’ Learning Achievement on Economics through Cooperative Learning Assisted By the Learning CD - Widjajati, Rahaju (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to improve students’ learning achievement. 32 students of grade X at Snior High School 2 Semarang were treated by classroom action research from May until June 2011. The research consisted of 2 cycles covering 4 stages, namely; planning, acting, observing and reflecting. It used cooperative learning strategy and descriptive analysis technique to compare observation result and reflection in each cycle. Findings show that cooperative learning methods can increase classically the learning mastery at grade X-8 by 75% in the first cycle with the average score is 70.22 and by 100% in the second cycle with the average score is 79.72.Then, it can be concluded that cooperative learning strategy by the learning CD can improve the cooperation, positive attitude, giving opinion and encourage students take parts in the fun atmosphere of learning process. Therefore, the strategy can improve learning outcomes on Economics in the Material of Consumption and Saving Functions.